The Longman companion to European decolonisation in the twentieth century - Chamberlain, Muriel Evelyn (Harlow, Essex, [England] Addison Wesley Longman Limited, 1998)
This addition to the Longman Companions to History series brings together in a single volume all the essential facts and figures relating to European decolonisation in the 20th century.
Sect. 1. The World in 1945. 1. The European Empires in 1945. The British Commonwealth and Empire in 1945. The French Empire in 1945. The Dutch Empire in 1945. The Portuguese Empire in 1945. The Spanish Empire in 1945. The Belgian Empire in 1945. The Italian Empire in 1945. 2. The League of Nations and the Mandate System. The Mandate System. The Mandated Territories. 3. Key Events of the Second World War. 4. The United Nations and Human Rights Declarations. Origins. The Structure of the United Nations (as relevant to Colonial Issues). Human Rights (and Similar) Declarations (of relevance to Colonial Issues) -- Sect. 2. Metropolitan Politics. Great Britain. France. The Netherlands. Portugal. Spain. Belgium.
Includes bibliographical references (pages 315-328) and index.
Keywords: Decolonization -- History; Europe -- Colonies -- History -- 20th century